Pengaruh Carbon Emission Disclosure, Eco-Efficiency dan Green Innovation Terhadap Nilai Perusahaan - Willy Sri Yuliandhari; Rr Sri Saraswati; Zaid Muhammad Rasid Safari (Owner : Riset dan Jurnal Akuntansi, 2023)
This study aims to determine the effect of carbon emission disclosures, eco-efficiency and green innovation on firm value. Firm value in this study was measured using Tobin's Q ratio. The population in this study are High Profile Industrial Companies listed on the Indonesia Stock Exchange (IDX) for the 2017-2021 period. The sample selection method in this study is purposive sampling. Based on sample selection criteria, the number of samples obtained was 16 companies with a total of 80 observations. The analytical technique used in this research is descriptive statistical analysis and panel data regression analysis using the Eviews application. The results of hypothesis testing show that simultaneously carbon emission disclosure, eco-efficiency and green innovation have a significant effect on firm value. Partially, carbon emission disclosures have a significant positive effect on firm value, green innovation has a significant negative effect on firm value, while eco-efficiency has no effect on firm value. This research is expected to be able to provide information about what factors can influence firm value both positively and negatively. Where this can be taken into consideration for companies to evaluate the company's performance and reference material for investors in making investment decisions in order to reduce the risk of loss.